DEVELOPMENT OF COLLECTIVE LEADERSHIP IN THEOLOGICAL EDUCATION IN POST-SOVIET PROTESTANTISM - Valentyn Synii ("Scientific Information Agency "Science-technologies-information" LLC, 2021)
The emergence of Baptist seminaries in Ukraine was influenced by Western churches or missions and in some cases by the Ukrainian diaspora, which had lived outside Ukraine for a long time. The decisive influence was exerted by representatives of churches, educational institutions and Christian universities in the United States. Seminaries went through a number of stages of their own development, during which the forms of collective leadership changed. The first stage is the emergence of seminaries and the harmonization of seminars to unified standards. In the first stage, immediately after the seminary was established, they had very friendly relations with local churches, the programs were very flexible and responded to the needs of the churches. Church leaders saw these initiatives as part of church ministry. The second stage is the extensive development of seminaries, by which the author means the involvement of additional resources in the work of seminaries and the growth of seminaries, associated with the number of students, and for some seminaries - the opening of branches or field programs. This type of growth was also due to the fact that seminaries began to become more independent of national churches, and partnerships with Western organizations became more formalized, which was most often seen in the participation of Western partners in the board of trustees. The third period is a reassessment of the work of seminaries. The beginning of this period is largely related to the global economic crisis of 2007-2008, and its result was the resumption of dialogue between seminaries and churches. The fourth period - institutional changes - is associated with the reaction of the Ukrainian state to the Bologna process and the adoption of the new Law of Ukraine "On Higher Education". The process of preparation for state accreditation and formation of a culture of openness in the national educational environment has begun.